2022
DOI: 10.1186/s12974-022-02568-x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of microRNAs reveals potential mechanisms of manual therapy alleviating neuropathic pain through microRNA-547-3p-mediated Map4k4/NF-κb signaling pathway

Abstract: Background Local neuroinflammation secondary to spinal nerve compression in lumbar disk herniation (LDH) is a key driver contributing to neuropathic pain. Manual therapy (MT), a widely used nonsurgical therapy, can relieve LDH-mediated pain by reducing inflammation. MT has attracted extensive attention; however, its mechanism remains poorly understood. MicroRNAs (miRNAs) are important regulators of pain signaling transduction, but are rarely reported in the chronic compression of dorsal root ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 67 publications
1
23
0
Order By: Relevance
“…Criteria (2)(3)(4)(5)(6)(7)(8)(9)(10)(11) were used to calculate the total PEDro score. Each criterion was scored as either 1 or 0 according to whether the criteria was met or not, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Criteria (2)(3)(4)(5)(6)(7)(8)(9)(10)(11) were used to calculate the total PEDro score. Each criterion was scored as either 1 or 0 according to whether the criteria was met or not, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Joint manipulations (such as chiropractic) involve a manual procedure directed thrust to move a joint past the physiological range of motion, without exceeding the anatomical limit, which could improve stiffness of the spinal joints by adjusting the stress of intervertebral joints surface ( 7 ). Manual therapy could intervene the transcription and translation of inflammation-related genes through miRNAs to improve neuroinflammation and alleviate neuropathic pain ( 8 ). Although several trials have reported that manual therapy had benefits in improving negative emotions and spinal pain in patients with IS, the efficacy of manual therapy in the management of IS remains controversial ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…When extracellular signals stimulate cells, NF-κB dimers are released from their inhibitor (IκB) and freely translocated into the nucleus to regulate the expression of their target genes ( 16 ). These responses are usually under the mediation of microRNAs (miRNAs) such as miR-547-3p and transcription factors ( 17 ).…”
Section: Klfs-mediated Molecular Regulationmentioning
confidence: 99%
“…14,15 A recent study simulated the treatment process of tuina manipulation and found that the analgesic effect on a neuropathic pain model may be related to the inflammatory pathway regulated by noncoding RNA. 16 Yijinjing is a type of traditional Chinese exercise that puts emphasis on the coordination of posture, meditation, and breathing. It is a moderately intense mind-body exercise that is easy to practice with few limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Two previous basic studies on animal experiments showed that pain behavior of mice was improved after simulating massage manipulation, which was associated with reduced peripheral inflammation mediated by the mechanosensitive channel protein Piezo and senescence-related pathways . A recent study simulated the treatment process of tuina manipulation and found that the analgesic effect on a neuropathic pain model may be related to the inflammatory pathway regulated by noncoding RNA . Yijinjing is a type of traditional Chinese exercise that puts emphasis on the coordination of posture, meditation, and breathing.…”
Section: Introductionmentioning
confidence: 99%